You have to use both equality axioms :
$\forall x \ (x=x)$ --- reflexivity
$\forall x \ \forall y \ (x=y) \to (\phi \to \phi')$ --- where $\phi'$ is obtained from $\phi$ by replacing $x$ in zero or more places by $y$ : replacement axiom.
Specifically, the instance of the replacement axiom needed is :
$\forall x \ \forall y \ ((x=y) \to [ (x=x) \to (y=x)])$.
The tableau must start with the axioms and the negation of the conclusion :
$\text F \ [ \ \forall x \ \forall y \ ((x=y) \to (y=x)) ]$.
Thus, you have first to "unpack" the leading quantifiers, correctly using $y_1$ and $x_1$ new, to get:
$\text F \ ((x_1=y_1) \to (y_1=x_1))$
and then :
$\text T \ (x_1=y_1)$
$\text F \ (y_1=x_1)$.
But this does not close.
1) $\text T \ \forall x \ (x=x)$ --- axiom
2) $\text T \ \forall x \ \forall y \ ((x=y) \to [ (x=x) \to (y=x)])$ --- axiom
3) $\text F \ \forall x \ \forall y \ ((x=y) \to (y=x))$ - negation of conclusion
4) $\text T \ (x_1=y_1)$ --- from 3)
5) $\text F \ (y_1=x_1)$ --- from 3)
6) $\text T \ (x_1=x_1)$ --- from 1)
7) $\text T \ ((x_1=y_1) \to [ (x_1=x_1) \to (y_1=x_1)])$ --- from 2).
Left branch:
8) $\text F \ (x_1=y_1)$ --- closes with 4).
Right branch :
9) $\text T \ ((x_1=x_1) \to (y_1=x_1))$.
Left branch :
10) $\text F \ (x_1=x_1)$ --- closes with 6).
Right branch :
11) $\text T \ (y_1=x_1)$ --- closes with 5).